BioMeQ-MD: Developing Biomechanical Interventions for Major Depression - Paul M Briley; Sean Lowton-Smith; Callum Osler; Tom Outram; Simon Briley (BJPsych Open)
Aims: Changes in body biomechanics – that is, changes in gait, posture, and balance – have been identified during episodes of major depressive disorder (MDD). Whilst biomechanical changes are related to the level of disability experienced by people with MDD, such changes are rarely asked about by clinicians or addressed directly by interventions. As part of a project studying whether interventions that target biomechanics might be helpful for MDD, we are conducting an initial non-patient study quantifying biomechanics, mood and anxiety, before and after physiotherapist-directed interventions.